Resilient religion: What good is religion for? - C.A.M. Hermans (Acta Theologica)
Good refers to the intrinsic value or telos (purpose) of religion. The author starts with the claim that religion keeps alive, in thinking, the awareness of ultimate meaning (“truth”); in actions, the focus on human dignity and the common good, and, in the heart of man, the longing for fulfilling happiness, peace of heart, and love. As spiritual beings, human beings transcend the given towards the telos or purpose of life. At the same time, human beings experience being thrown in the limits of time and space. When the synthesis between the self as open to the ultimate and the self as limited is not realised, human beings experience a heartbreaking adversity. The intrinsic value of religion is the promotion of this synthesis. The author analyses three mediating processes of resilience that promote the possibility of a synthesis: the recognition of contingency, the experience of fulfilling happiness, and the wonder of possibilisation (new beginnings). Finally, the author links resilience to the concept of God as creator.